Design and Rationale of the RIPCORD 2 Trial (Does Routine Pressure Wire Assessment Influence Management Strategy at Coronary Angiography for Diagnosis of Chest Pain?): A Randomized Controlled Trial to Compare Routine Pressure Wire Assessment With Conventional Angiography in the Management of Patients With Coronary Artery Disease. Issue 2 (February 2018) - Elguindy, Mostafa; Stables, Rod; Nicholas, Zoe; Kemp, Ian; Curzen, Nick
Abstract : Background: Investigation of anginal chest pain has traditionally involved either assessment of the coronary anatomy by angiography or noninvasive testing for reversible ischemia. Invasive pressure wire assessment at the time of angiography offers information on both anatomy and physiology. Fractional flow reserve–guided percutaneous coronary intervention is associated with lower resource utilization and improved clinical outcome compared with angiographic guidance alone. However, the value of routine fractional flow reserve of all major coronary vessels at the time of diagnostic angiography has not been established in a randomized trial despite persuasive observational data. A change in practice to routine fractional flow reserve assessment of all major vessels during diagnostic angiography would require evidence not just of clinical benefit but also of cost effectiveness. This randomized trial aims to test that strategy. Methods and Results: RIPCORD 2 (Does Routine Pressure Wire Assessment Influence Management Strategy at Coronary Angiography for Diagnosis of Chest Pain?) is an 1100 patient prospective, multicenter, randomized trial. Participants are randomized, after initial coronary angiography, and in equal proportion, to assessment and management according to (1) conventional angiography only or (2) additional routine pressure wire assessment in all epicardial vessels of sufficient size to be amenable to revascularization. The primary economic outcome measure will be a comparison of healthcare costs at 1 year. The primary quality-of-life outcome measure analysis will compare patient-reported quality-of-life scores at 1 year. Secondary outcome measures include clinical events at 1 year, management strategy (optimal medical therapy with or without revascularization), and angina status at 1 year according to Canadian Cardiovascular Society angina grade. Conclusions: The aim of the RIPCORD 2 trial is to assess whether a strategy of routine fractional flow reserve–guided assessment and management of all major coronary arteries will be associated with more effective resource utilization, improved quality of life, and better clinical outcome, compared with angiographic guidance alone. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02892903. Abstract : Supplemental Digital Content is available in the text.